2017
DOI: 10.1038/srep45092
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the immunodominant 33-mer peptide from α-gliadin in wheat flours by liquid chromatography tandem mass spectrometry

Abstract: Coeliac disease (CD) is triggered by the ingestion of gluten proteins from wheat, rye, and barley. The 33-mer peptide from α2-gliadin has frequently been described as the most important CD-immunogenic sequence within gluten. However, from more than 890 published amino acid sequences of α-gliadins, only 19 sequences contain the 33-mer. In order to make a precise assessment of the importance of the 33-mer, it is necessary to elucidate which wheat species and cultivars contain the peptide and at which concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 43 publications
2
61
2
1
Order By: Relevance
“…Recently, the quantification of the 33‐mer by liquid chromatography tandem mass spectrometry in different wheat species and cultivars has been performed. This report shows that after proteolysis, the 33‐mer remains in the range of 91 to 603 μg g −1 in wheat flour, which justifies the importance of this fragment in the human diet . This highly proteolytic‐resistant peptide harbors six epitopes that are in part overlapping.…”
Section: Identification Of Gliadin Peptides and Their Pathological Rolementioning
confidence: 69%
“…Recently, the quantification of the 33‐mer by liquid chromatography tandem mass spectrometry in different wheat species and cultivars has been performed. This report shows that after proteolysis, the 33‐mer remains in the range of 91 to 603 μg g −1 in wheat flour, which justifies the importance of this fragment in the human diet . This highly proteolytic‐resistant peptide harbors six epitopes that are in part overlapping.…”
Section: Identification Of Gliadin Peptides and Their Pathological Rolementioning
confidence: 69%
“…There is evidence for changes in gluten protein composition (132)(133)(134) with decreasing contents of gliadins and total gluten, but increasing contents of glutenins from diploid to tetraploid and hexaploid wheats. However, within bread wheat or durum wheat, there were no clear differences in the contents of selected CD-active epitopes between modern cultivars and landraces not subjected to breeding (135)(136)(137)(138). All studies consistently reported a significant effect of environmental conditions on the expression of CD-immunogenic peptides, with e.g., low or high cultivation temperatures affecting the expression of immunostimulatory proteins in different ways (124).…”
Section: Update On Gluten Composition Of Wheat and Methods For Modifimentioning
confidence: 95%
“…Different studies have shown that tetraploid wheat are less immunogenic than hexaploid wheat (285)(286)(287). In one study, Schalk et al (284) did not detect any 33-mer peptide sequence in two durum wheat cultivars and two emmer cultivars (genome AABB) by using liquid chromatography tandem mass spectrometry (LC-MS/MS) and attributed this to the absence of chromosome 6D. Similarly, Molberg et al (288) showed absence of 33-mer peptide sequence encoded by α-gliadin genes in diploid einkorn (including T. monococcum, T. uraru, and A. speltoides).…”
Section: Is There Difference Between Diploid Tetraploid or Hexaploimentioning
confidence: 99%